La frammentazione del paesaggio periurbano - Gabriele, Paolinelli (Scuole di dottorato, 2003)
This book presents the results of a study on the fragmentation of the suburban territory in the Florentine plain, developed in the framework of the Florence University PhD course in Landscape Design. Thus the landscape on the western edge of the urban centre becomes a case study for evolving from the applications to the quest for theoretical and methodological elements. What emerges clearly from this is the importance of the design mentality as an essential cultural value for the drafting of policies of active conservation, retrieval and modification of the landscape.